Concurrent validity of a low‐cost and time‐efficient clinical sensory test battery to evaluate somatosensory dysfunction. (28th August 2019) - Zhu, Guan Cheng; Böttger, Karina; Slater, Helen; Cook, Chad; Farrell, Scott F.; Hailey, Louise; Tampin, Brigitte; Schmid, Annina B.
Abstract: Background: This study describes a low‐cost and time‐efficient clinical sensory test (CST) battery and evaluates its concurrent validity as a screening tool to detect somatosensory dysfunction as determined using quantitative sensory testing (QST). Method: Three patient cohorts with carpal tunnel syndrome (CTS, n  = 76), non‐specific neck and arm pain (NSNAP, n  = 40) and lumbar radicular pain/radiculopathy (LR, n  = 26) were included. The CST consisted of 13 tests, each corresponding to a QST parameter and evaluating a broad spectrum of sensory functions using thermal (coins, ice cube, hot test tube) and mechanical (cotton wool, von Frey hairs, tuning fork, toothpicks, thumb and eraser pressure) detection and pain thresholds testing both loss and gain of function. Agreement rate, statistical significance and strength of correlation (phi coefficient) between CST and QST parameters were calculated. Results: Several CST parameters (cold, warm and mechanical detection thresholds as well as cold and pressure pain thresholds) were significantly correlated with QST, with a majority demonstrating >60% agreement rates and moderate to relatively strong correlations. However, agreement varied among cohorts. Gain of function parameters showed stronger agreement in the CTS and LR cohorts, whereas loss of function parameters had better agreement in the NSNAP cohort. Other CST parameters (16 mN von Frey tests, vibration detection, heat and mechanical pain thresholds, wind‐up ratio) did not significantly correlate with QST. Conclusion: Some of the tests in the CST could help detect somatosensory dysfunction as determined with QST. Parts of the CST could therefore be used as a low‐cost screening tool in a clinical setting. Significance: Quantitative sensory testing, albeit considered the gold standard to evaluate somatosensory dysfunction, requires expensive equipment, specialized examiner training and substantial time commitment which challenges its use in a clinical setting. Our study describes a CST as a low‐cost and time‐efficient alternative. Some of the CST tools (cold, warm, mechanical detection thresholds; pressure pain thresholds) significantly correlated with the respective QST parameters, suggesting that they may be useful in a clinical setting to detect sensory dysfunction.